Cytosolic Nudix Hydrolase 1 Is Involved in Geranyl β-Primeveroside Production in Tea - Zhou, Hanchen; Wang, Shijie; Xie, Hao-Fen; Liu, Guofeng; Shamala, Lubobi Ferdinand; Pang, Jingyi; Zhang, Zhengzhu; Ling, Tie-Jun; Wei, Shu (Frontiers in Plant Science, 2022)
Geraniol is a potent tea odorant and exists mainly as geranyl glycoside in Camellia sinensis. Understanding the mechanisms of geraniol biosynthesis at molecular levels in tea plants is of great importance for practical improvement of tea aroma. In this study, geraniol and its glycosides from tea plants were examined using liquid chromatography coupled with mass spectrometry. Two candidate geraniol synthase (GES) genes (CsTPS) and two Nudix hydrolase genes (CsNUDX1-cyto and CsNUDX1-chlo) from the tea genome were functionally investigated through gene transcription manipulation and gene chemical product analyses. Our data showed that in tea leaves, levels of geranyl β-primeveroside were dramatically higher than those of geranyl β-glucoside, while free geraniol was undetectable in this study. A tempo-spatial variation of geranyl β-primeveroside abundance in tea plants existed, with high levels in young and green tissues and low levels in mature or non-green tissues. Cytosolic CsNUDX1-cyto showed higher hydrolysis activity of geranyl-pyrophosphate to geranyl-monophosphate (GP) in vitro than did chloroplastidial CsNUDX1-chlo. A transgenic study revealed that expression of CsNUDX1-cyto resulted in significantly more geranyl β-primeveroside in transgenic Nicotiana benthamiana compared with non-transgenic wild-type, whereas expression of CsNUDX1-chlo had no effect. An antisense oligo-deoxynucleotide study confirmed that suppression of CsNUDX1-cyto transcription in tea shoots led to a significant decrease in geranyl β-primeveroside abundance. Additionally, CsNUDX1-cyto transcript levels and geranyl β-primeveroside abundances shared the same tempo-spatial patterns in different organs in the tea cultivar “Shucha Zao,” indicating that CsNUDX1-cyto is important for geranyl β-primeveroside formation in tea plants. Results also suggested that neither of the two candidate GES genes in tea plants did not function as GES in transgenic N. benthamiana. All our data indicated that CsNUDX1-cyto is involved in geranyl β-primeveroside production in tea plants. Our speculation about possible conversion from the chemical product of CsNUDX1-cyto to geranyl β-primeveroside in plants was also discussed.